Genomes of the Bacterial Endosymbionts of Carrot Psyllid Trioza apicalis Suggest Complementary Biosynthetic Capabilities - Thompson, Sarah; Wang, Jinhui; Schott, Thomas; Nissinen, Riitta; Haapalainen, Minna (Springer Science and Business Media LLC, 2025)
Carrot psyllid Trioza apicalis is a serious pest of cultivated carrot and also a vector of the plant pathogen 'Candidatus Liberibacter solanacearum' (Lso). To find out whether T. apicalis harbours other species of bacteria that might affect the Lso infection rate, the bacterial communities and metagenome in T. apicalis were studied. Lso haplotype C was detected in a third of the psyllids sampled, at different relative amounts. Surprisingly, T. apicalis was found to harbour only one secondary endosymbiont, a previously unknown species of gamma proteobacterium endosymbiont (Gpe), beside the primary endosymbiont 'Candidatus Carsonella ruddii' (CCr). The relative abundancies of these two endosymbionts were approximately equal. The genomes of CCr, Gpe and Lso were assembled from a T. apicalis metagenome sample. Based on the 16S rRNA gene, the closest relative of Gpe of T. apicalis could be a secondary endosymbiont of Trioza magnoliae. The 253.171 kb Gpe genome contains all the tRNA and rRNA genes and most of the protein-coding genes required for DNA replication, transcription and translation, but it lacks most of the genes for amino acid biosynthesis. Gpe has no genes encoding cell wall peptidoglycan synthesis, suggesting it has no cell wall, and could thus live as an intracellular endosymbiont. Like the CCr of other psyllids, CCr of T. apicalis retains a broad amino acid biosynthetic capacity, whilst lacking many genes required for DNA replication and repair and for transcription and translation. These findings suggest that these two endosymbionts of T. apicalis are complementary in their biosynthetic capabilities.